A Scoping Review of Generative AI Reenactment in Biology Education: Approaches, Practices, and Challenges - Maulana Arsyadani Bintang Pratama Putra; Slamet Hariyadi (Biosel Biology Science and Education, 2026)
The integration of Generative AI (GenAI) Reenactment in biology education offers potential for interactive simulations, yet details regarding its practical use and effectiveness outcomes have not been comprehensively documented. This study aims to map the technological approaches, pedagogical practices, and challenges of using GenAI Reenactment in biology learning through a scoping review method. The method utilizes the Arksey & O’Malley and PRISMA-ScR frameworks, enriched with the Reflexive Thematic Analysis approach by Braun and Clarke. A literature search (2023–2025) across reputable databases yielded 4 primary articles meeting the inclusion criteria. Data analysis identified three key themes: (1) Evolution of Technological Approaches, ranging from text-based Large Language Models for role-playing interactions to indications of integration with Virtual Reality (VR) and Augmented Reality (AR); (2) Transformation of Pedagogical Practices, where GenAI simulates roles as a self-directed learning tool and potentially as a Virtual Teaching Assistant (VTA) in laboratories; and (3) Multidimensional Challenges, highlighting risks of declining psychomotor skills and student communication originality due to reliance on instant answers. It can be concluded that GenAI Reenactment demonstrates potential as an interactive evolution of previous visualization technologies, necessitating a hybrid supervision model.  Keywords: Generative AI Reenactment, Biology Education, Virtual Teaching Assistant, Reflexive Thematic Analysis.